THE INTERPLAY BETWEEN GLOBAL CONSULTING SERVICES AND ECONOMIC GROWTH - Volodymyr V. Tokar (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The Covid-pandemic forces governments, individuals, and legal entities to transit from business-as-usual approach to digital, inclusive, innovative, and adaptive management and producing models. Maintaining the old ways of decision-making became increasingly difficult, if not impossible. The lack of adequate knowledge, know-how and time deficit increases the demand for professional advice from peers or individuals and companies specialized in consulting services in different spheres, including management in general, personnel, information technologies, security, etc. The global consulting services industry in general and its most successful representatives, both individuals and firms, seem to prosper in any case, but the question is whether their consultancy really improves business results and stimulates economic growth. The article aims are disclosing the connection between global consulting services and economic development applying correlation analysis to the size of global consulting services market and the World Bank’s data on GDP. The paper discloses recent changes in the size of global consulting services market and world GDP growth. The size of global consulting services markets constantly grew and the change equaled 44.4 percent in 2011–2020. Financial advisory and operations consultancy were the fastest growing segments demonstrating the increase of 54.5 and 53.6 percent, respectively. The global GDP increased by 14.2 during this period reaching $83.8 trillion in 2020 and showing the peak of $87.6 trillion in 2019. Our calculations have shown that the linear correlation coefficient of the size of global consulting services market and world GDP is statistically significant. Therefore, there is a direct and strong connection between consulting services and economic growth, namely the global GDP. The increase of the size of global consulting services market by 1 unit ($1 billion) causes the average increase of the world GDP by 0.139 units ($ trillion). The perspectives of further investigations embrace the analysis of efficiency of consulting services in key segments of the global market, namely strategy, operations, human resources, financial advisory, and technology